Sustainable Maritime of Onshore Power Supply Systems for Ships in Thai Ports - Kanokwannakhon, Phatthawut; Muangpan, Thanyaphat; Makkawan, Kittisak (Sustainable Marine Structures, 2026)
Maritime transport faces escalating decarbonization pressure, prompting ports and shipping lines to evaluate onshore power supply (OPS) as a near-term abatement option for hoteling (at-berth) emissions. This study assesses the feasibility of implementing OPS for ship berthing at Bangkok Port, Thailand, using a sequential mixed-methods design. Qualitative evidence from semi-structured interviews with 26 shipping lines and 3 Port Authority of Thailand (PAT) respondents, combined with a Strengths, Weaknesses, Opportunities, and Threats (SWOT)-based contextual assessment, identifies readiness conditions and adoption constraints. A 30-year discounted cash-flow appraisal evaluates investor-side performance (NPV, IRR, and payback) for a pilot at container berths 20A and 20F and tests tariff mark-up sensitivity under 2022–2024 fuel and electricity price conditions. A socio-economic appraisal monetizes avoided air pollutants (PM2.5, NOx, SOx) and CO2 using AIS-based hoteling profiles and recognized emission-factor approaches, and reports EIRR. Results show that OPS is financially unattractive for the port operator in all scenarios (base case: NPV = −4.61 million USD; IRR = −3.38%); breakeven would require an ~115% tariff mark-up, which may reduce uptake. In contrast, the economic case is positive (EIRR = 7.78% at a 7% social discount rate), yielding an estimated net social benefit of 417,885 USD/year and avoiding 885.46 tCO2/year for a pilot demand of ~1.25 GWh/year. These findings indicate a coordination gap between infrastructure investment and vessel uptake, implying a need for targeted public co-financing, transparent tariff design, and phased deployment linked to demonstrated demand. The study contributes policy-relevant evidence for medium-scale ports in emerging policy settings where social benefits may exceed private returns. ER